1983
DOI: 10.1104/pp.73.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine Synthesis in Pea Leaves, and the Occurrence of an Asparagine Synthetase Inhibitor

Abstract: Asparagine is present in the mature leaves of young pea (Pisum sativum cv Little Marvel) seedlings, and is synthesized in detached shoots. This accumulation and synthesis is greatly enhanced by darkening. In detached control shoots, '4Claspartate was metabolized predominantly to organic acids and, as other workers have shown, there was little labeling of asparagine (after 5 hours, 3.1% of metabolized label).Addition of the aminotransferase inhibitor aminooxyacetate decreased the flow of aspartate carbon to org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 18 publications
2
42
1
2
Order By: Relevance
“…Again, the labeling of homoserine bears little relationship to the labeling of aspartate. It is interesting to note that succinate provided carbon for the synthesis of asparagine which is increased in darkness (3). AOA prevented homoserine synthesis from succinate (Table V).…”
Section: Resultsmentioning
confidence: 99%
“…Again, the labeling of homoserine bears little relationship to the labeling of aspartate. It is interesting to note that succinate provided carbon for the synthesis of asparagine which is increased in darkness (3). AOA prevented homoserine synthesis from succinate (Table V).…”
Section: Resultsmentioning
confidence: 99%
“…The classic example of Asn accumulation in response to stress is documented in asparagus spears in which concentrations increase five-to 1 O-fold within 24 hr of harvest (King et al, 1990). Pea leaves darkened for 72 hr have an -15-:old increase in free Asn compared with leaves exposed to the normal photoperiod (Joy et al, 1983). Similarly, sugar-starved maize root tips (Brouquisse et al, 1992) and sycamore suspension cells (Genix et al, 1990) have markedly higher amounts of free Asn compared with control tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that AS enzyme activity in pea leaves (Joy et al, 1983) and mRNA in leaves of pea (Tsai and Coruzzi, 1990), Nicofiana spp (Tsai and Coruzzi, 1991), and Arabidopsis (Lam et al, 1994) are repressed by light. In contrast, AS expression in asparagus (Davies and King, 1993) and maize roots (Chevalier et al, 1996) appears to be unaffected by light.…”
Section: Organ-specwic Expression Of Alfalfa Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise study of ASN1 enzyme activities from plant extracts is hampered by instability of the AS enzyme in vitro (Sieciechowicz et al, 1988); copurification of a heat-stable, dialyzable inhibitor (Kern and Chrispeels, 1978;Joy et al, 1983); and the presence of contaminating asparaginase activity in plant extracts (Huber and Streeter, 1985) and the existence of multiple isoenzymes . Besides, our ultimate goal is to study the changes in amino acid metabolism and nitrogen status; therefore, we directly determined the steady-state levels of free Asn (product of AS enzymes) in leaves and siliques of 35S-ASN1 plants and compared them with control wild type (Col-0) or wild type transformed with an empty vector (359-2C-8; Fig.…”
Section: Construction Of Transgenic Arabidopsis Overexpressing Asn1mentioning
confidence: 99%